Legal Legality of Pregnant Marriage in Indonesia Study on the Application of Khi Article 53 in Mlati District Prospective Fatwa Abno Taymiyah - Binarsa Binarsa (Jurnal Indonesia Sosial Teknologi, 2024)
Formulating the Compilation of Islamic Law is inseparable from the growth and development of Islamic law and the institution of the Religious Courts before and after the Indonesian people proclaimed their independence on August 17, 1945. So the Indonesian people who are Muslim, The Religious Courts, the Ulama, and all components related to the determination of KHI agree that the compilation of Islamic Law is Islamic law, which is the source of law to solve the problem of pregnant marriage in Indonesia. However, in the day-to-day application of this decree, an interesting problem occurred, which was partly that the Mlati community did tajwid al-Nikah. A question! Why did they remarry? They answered that because they considered the marriage they were having at KUA, there were doubts, and they were not legal. "This event is repeated, so that if accumulated since 2017-2019 in the District of Mlati, as much as 75 percent of those who do tajdii du al-Nikah. Based on this background, the research question is: How is the application of KHI in article 53 in community life in the district of Mlati perspective in Ibnu Taimiyyah review, and what references are used to compile compilation of Islamic Law? The theoretical framework used is the theory of legal effectiveness, the view of mazhab-maz hab Islam, including al-Hanafiyyah, al-Malikiyyah, al-Syafi'iyyah, al-Hanbaliyyah, and mazhab al-Zahiriyyah and Ibnu Taimiyyah's though. The research methodology is library research. The nature of this dissertation research is descriptive research and verification research. This research approach uses a philosophical approach, a historical approach, and a normative approach. The conclusions are: The application of pregnant marriage in the sub-district of Mlati Sleman from the perspective of Ibnu Taimiyyah's fatwa is invalid, and are 13 books used to compile the compilation of Islamic law.